Use of health locus of control on self‐management and HbA1c in patients with type 2 diabetes - Lingxiao Zhu; Qifang Shi; Yue Zeng; Tong Ma; Haomiao Li; Dilihumaer Kuerban; Sarita Hamal; Meng Li (Wiley, 2022)
Abstract Aim To assess the effects of health locus of control‐based education programme (HLCEP) on self‐management, health locus of control and glycated haemoglobin (HbA1c) among type 2 diabetes mellitus (T2DM). Design Quasi‐experimental study. Methods The study recruited 120 T2DM participants from May-September 2020. The control group received one‐week in‐hospital care and 12‐week follow‐up. The intervention group received additional HLCEP. The self‐management and the health locus of control were measured by using the Summary of Diabetes Self‐care Activities and the Multidimensional Health Locus of Control at baseline and the 4th and 12th week after discharge. The HbA1c was collected at baseline and the 12th week after discharge. The generalized estimating equation analysis was performed to assess the intervention effects. Results The intervention group has statistically significantly higher scores on the overall level of self‐management, dietary management, foot care, medication management and internal health locus of control, while a lower HbA1c level than the control group.